TMT environmental cognition and greenwashing behavior: evidence from Chinese firms - Jia-Wen, Zou; Miaoshuo, (Frontiers in Environmental Science, 2024)
The influencing factors of corporate greenwashing have consistently captivated scholarly attention. Drawing from Upper Echelons Theory and Strategic Recognition Theory, this study proposes that the green cognition of top management plays a critical role in shaping greenwashing practices. Furthermore, it is argued that this relationship may be moderated by factors such as political connections and the stringency of environmental regulations. To clarify these issues, this study utilizes a panel model with samples of Chinese listed firms that contain fundamental data and variables from 2012 to 2020. The results show that: 1) TMT environmental cognition restrain greenwashing behavior significantly by promoting genuine environmental efforts. 2) The inhibitory effect of TMT environmental cognition on greenwashing behavior is more pronounced in firms without political connections than those with political connections. 3) TMT environmental cognition has a significantly positive impact on environmental disclosure scores for private owned or political connection firms, except for state-owned or no political connection firms. 4) The level of political connection of firms and the intensity of environmental regulations have respectively strengthened or weakened the link between TMT environmental cognition and greenwashing behavior.